Recursive computational algorithms for a set of block pulse operational matrices - JIANG, Z. H.; SCHAUFELBERGER, W. (International journal of systems science, 1992)
A set of integral operational matrices, which are superior to the conventional and generalized integral operational matrices in the identification of time-varying linear systems via block pulse functions, can be calculated efficiently by the new recursive computational algorithms which are proposed in this paper. As the basis of these algorithms, the constant difference properties of entries of the set of operational matrices are proved. And as the advantage of these algorithms, the reduction of their computational size is discussed. The proposed algorithms are especially useful when the number of block pulses is large in realistic applications of the block pulse function method.